Motivational Interview Techniques and the Effectiveness of Intervention Programs With Perpetrators of Intimate Partner Violence: A Systematic Review - Pinto E Silva, Teresa (2023)
Intimate Partner Violence (IPV) is widely recognized as a severe public health issue. Perpetrators’ Intervention Programs (PIPs) have been essential to prevent recidivism, and the incorporation of Motivational Interview Techniques (MIT) has shown to be an added value in this area. Objective: The present systematic review aims to analyze the incorporation of MIT (i.e., pre-treatment, isolated treatment, and conjoined with PIPs) in interventions with IPV perpetrators and its potential impact on their behavior and attitudes regarding motivation for change and treatment compliance. Method: The following research equation was used: “Intimate Partner Violence” AND (“Perpetrator” OR “Batterer” OR “Offender”) AND (“Motivation” OR “Motivational Interview”) AND (“Intervention” OR “Intervention Program” OR “Batterer Intervention Program”) AND (“Effectiveness OR “Program Effectiveness”); in four separate databases: PubMed, PsycINFO, Science Direct, and EBSCO. Studies in English, Portuguese, and Spanish were included, and 15 were identified according to the defined inclusion criteria. Results: Studies demonstrated that MIT increases attendance rates, treatment adherence, motivation for change, and behavioral and attitudinal outcomes. More specifically, MIT showed greater effectiveness among participants with low readiness to change and in the early stages of change. Conclusion: This systematic review corroborates the importance of incorporating MIT in PIPs to improve intervention efficacy.